2019
DOI: 10.1096/fj.201900092r
|View full text |Cite
|
Sign up to set email alerts
|

The key genes, phosphoproteins, processes, and pathways affected by efavirenz‐activated CYP46A1 in the amyloid‐decreasing paradigm of efavirenz treatment

Abstract: Efavirenz (EFV) is an anti‐HIV drug, and cytochrome P450 46A1 (CYP46A1) is the major brain cholesterol hydroxylase. Previously, we discovered that EFV activates CYP46A1 and improves behavioral performance in 5XFAD mice, an Alzheimer's disease model. Herein, the unbiased omics and other approaches were used to study 5XFAD mice in the amyloid‐decreasing paradigm of CYP46A1 activation by EFV. These approaches revealed increases in the brain levels of postsynaptic density protein 95, gephyrin, synaptophysin, synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 178 publications
2
40
0
Order By: Relevance
“…One of the reported phenotypes of CH24H-KO mice is an impairment in learning 47 . Conversely, it has been reported that activation of CH24H has pro-cognitive potential 20,48 . Three-month-old APP/PS1-Tg animals were treated with soticlestat and underwent the Y-maze test.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…One of the reported phenotypes of CH24H-KO mice is an impairment in learning 47 . Conversely, it has been reported that activation of CH24H has pro-cognitive potential 20,48 . Three-month-old APP/PS1-Tg animals were treated with soticlestat and underwent the Y-maze test.…”
Section: Discussionmentioning
confidence: 95%
“…S7). This observation may disagree with the cognitive benefits of efavirenz, a reverse transcriptase inhibitor known for CH24H activation 20,48 . It should be noted that the effects of efavirenz on cognition are apparently associated with improvement in amyloid pathology.…”
Section: Discussionmentioning
confidence: 96%
“…Studies in mice revealed a broad therapeutic potential of increased CYP46A1 activity for various neurodegenerative disorders such as Alzheimer’s and Huntington’s diseases, Niemann-Pick disease type C and spinocerebellar ataxia ( Hudry et al , 2010 ; Burlot et al , 2015 ; Boussicault et al , 2016 ; Mast et al , 2017 b ; Kacher et al , 2019 ; Mitroi et al , 2019 ; Nóbrega et al , 2019 ; Petrov et al , 2019 b ). Even glioblastoma, an aggressive brain tumour, was found to be inhibited in mice by pharmacologic CYP46A1 activation ( Han et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effects on the amyloid β levels (Aβ) were the treatment paradigm-specific, either Aβ decreasing or not changing. Studies by the omics approaches documented altered protein phosphorylation in EFV-treated 5XFAD mice and pointed to the effects on synaptic function, inflammation, microglia phenotype, oxidative stress, cellular hypoxia, ubiquitin-proteasome system, autophagy and apoptosis ( Petrov et al , 2019 b ). Protein phosphorylation was also altered in Cyp46a1 −/− mice ( Mast et al , 2017 a ), and the affected processes overlapped in part with those in EFV-treated 5XFAD mice (synaptic transmission, ubiquitination and cytoskeleton maintenance).…”
Section: Introductionmentioning
confidence: 99%
“…appear to lend anti-apoptotic activities to these lipoproteins Previous studies reported both pro-and anti-apoptotic effects of 24-OHC(55)(56)(57)(58)(59). Possibly, the discrepant findings are due to differences in concentrations (micromolar vs. nanomolar) or the origin (endogenously produced vs. exogenously supplied) of the oxysterol in the various cell culture models.…”
mentioning
confidence: 99%